2009
DOI: 10.1111/j.1745-6606.2009.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Providing Parents with Online Privacy Information: Approaches in the US and the UK

Abstract: Policy makers are faced with the task of ensuring that parents are offered information on children's Web sites to help them reduce their children's online privacy risks. This exploratory research compares the approaches of two countries with different regulatory philosophies regarding children's privacy: the United States, with a limited and sectoral approach to general privacy but a formalized approach to children's online privacy, and the United Kingdom, with a comprehensive overarching approach to privacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In contrast, more recent studies observed that a majority of children’s websites processing personal data also posted a privacy statement (Cai and Zhao, 2010; Stanaland and others, 2009). Although information on the data being collected and its uses was mostly included, some aspects, however, were less present, most noticeably in the areas of the security of children’s personal data, users’ choice to opt out, namely to object to specific data uses, or delete information, and details regarding parental rights and access (Stanaland and others, 2009).…”
Section: Lack Of Compliancementioning
confidence: 96%
“…In contrast, more recent studies observed that a majority of children’s websites processing personal data also posted a privacy statement (Cai and Zhao, 2010; Stanaland and others, 2009). Although information on the data being collected and its uses was mostly included, some aspects, however, were less present, most noticeably in the areas of the security of children’s personal data, users’ choice to opt out, namely to object to specific data uses, or delete information, and details regarding parental rights and access (Stanaland and others, 2009).…”
Section: Lack Of Compliancementioning
confidence: 96%
“…The Directive on Data Protection requires European websites to disclose the use of cookies and recommends that privacy notices to be short and easy for consumers to understand [3]. However, as showed in Table I, the policy instrument used by European Union (EU) is different in Denmark, Sweden and UK.…”
Section: A Regional Privacy Policymentioning
confidence: 99%
“…Much fewer had basic elements of privacy policies, such as assurances that the data collected is secure, allowing people to access data collected about them, providing people with a choice to choose or use their information, and providing notice prior to collection of data. Stanaland, Lwin, and Leong (2009) had more recent data of comparison of the top 100 children's websites from the United States and the United Kingdom. Data showed that 95 percent of American websites had a privacy policy and 83 percent of United Kingdom websites had such a policy.…”
Section: Prior Comparative Research On Privacymentioning
confidence: 99%
“…The United States has adopted an informal self-regulatory approach (Stanaland et al, 2009). Historically, there has been a greater concern over federal and state government invasions of privacy than private company invasions of privacy (Harrison, 2000).…”
Section: Privacy Concernsmentioning
confidence: 99%